THE RELEVANCE OF IGOR LUKASHUK’S SCIENTIFIC LEGACY IN INTERNATIONAL LAW AMID THE RUSSIAN FULL-SCALE INVASION OF UKRAINE - Yaremchuk, Vitalii (Yuriy Fedkovych Chernivtsi National University Chernivtsi – Ukraine, 2023)
The ineffectiveness of institutional and legal mechanisms, such as the UN, non-observance of international law principles by states whose status assumed a leading role in the maintenance of international peace and security, and the inability of international legal mechanisms to effectively combat international legal violations are making it ever more challenging to discuss international law reform. Dr. Lukashuk’s ideas and perspectives on nature and the evolution of international law extend well beyond national boundaries or historical phases. He was a skilled scholar in the subject of international law, and the importance of his views is expanding quickly